PENGAWASAN TERHADAP PENERIMAAN PESERTA DIDIK BARU (PPDB) ONLINE BERDASARKAN PERATURAN GUBERNUR RIAU NOMOR 11 TAHUN 2023 - Putri, Melza Adika; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
In this research, there are several problem phenomena that will be raised in 2023 regarding PPDB Online at the high school level, the uneven distribution of schools and the limited quota available in state schools are the main causes of competition in PPDB at the high school level, giving rise to several problems, especially because there is still public perception. regarding favorite schools and non-favorite schools which causes parents and guardians to compete to enroll their children in schools that are considered favorites and ultimately causes various problems to arise. Such as the discovery of 31 fake Family Cards during PPDB Online registration at SMA Negeri 8 Pekanbaru City, there were addresses that did not match the coordinates and so on. Therefore, PPDB Online at the high school level in Pekanbaru city must continue to be monitored. The Ombudsman as a public service supervisory institution must continue to supervise the implementation of PPDB Online considering that PPDB Online is also included in public services in the education sector. This research uses qualitative research methods with a descriptive approach. The types of data used are primary data and secondary data, primary data is obtained directly from original sources without going through intermediaries. Meanwhile, secondary data is obtained not from the first source, and can be in the form of media to support primary data. Data collection techniques were carried out using interviews and documentation. The results of this research show that the Riau Province Ombudsman has carried out routine supervision every year by carrying out preliminary supervision, concurrent supervision, and feedback supervision which was carried out from before the Online PPDB was implemented until the online PPDB was completed. However, unfortunately in 2023, the preliminary supervision carried out by the Ombudsman will only be limited to coordinating, but not participating in supervising the formation of the PPDB committee and PPDB socialization. The Ombudsman only focuses on receiving reports from the public but lacks preliminary supervision. Keywords: Supervision, Ombudsman, PPDB